Die Biographie - Mode oder Universalie? : zu Geschichte und Konzept einer Gattung in der Kunstgeschichte - Böckem, Beate; Peters, Olaf; Schellewald, Barbara (Schriften zur modernen Kunsthistoriographie, 2016)
In the field of art, concepts in which a work has been considered from the perspective the artists themselves have long been in fashion. They are reflected in how highly artists' statements are valued, and characterize the working methods of art history and criticism. On this basis, the publication looks at the different genres of the biography and its periphery. It examines monographs that connect life and work in the form of an artist's biography, as well as the "masquerade" of the autobiography and what artists say about themselves and their work in interviews or in programmatic statements. It also takes an in-depth look at the memoirs of art historians and the academic biography of the scholar.
Keywords: Art : Historiography; Artists : Historiography